Factors Affecting The Length of Hospitalization at The Patients Admit to Emergency Department With Gastrointestinal Bleeding - Cander, Başar; Ertekin, Birsen; Kara, Hasan; Gül, Mehmet; Dündar, Defne; Koçak, Sedat; Girişgin, Sadık (Fırat University, 2011)
Objective: Gastrointestinal system bleeding are generally emergency manifestations. Mortality rate is between 5-12%. In this study, we aimed to evaluate the relationship between leucocyte, CRP values at admission, the endoscopic findings and the duration of hospital stay of the patients, those apply to our clinic by reason of upper gastrointestinal tract bleedings. Material and Methods: The patients with GIS bleeding those have been applied to Selçuk University Meram Medical Faculty Emergency Department between September 2008 and December 2008 have been included to this study. The patients have been assessed in terms of age, sex, length of stay, CRP and leucocyte values at admission and the endoscopic findings. Results: Total of 30 patients have been included to our study. The patients with lower gastrointestinal bleeding and with varice bleeding were excluded from the study. 33% of them were female and 67% of them were male. Average leucocyte values of the patients were 11,06±4,06 and average CRP values were 35,77±26,56. Average length of stay for these patients has been determined as 6,40±6,17. The most common symptoms have been admitted because of upper gastrointestinal bleeding have been determined as 70% phase 3, 3.3% phase 2b, 6.7% phase 2a, 13.3% phase 1b, 6.7% phase 1a . Conclusion: A significant correlation between the hospitalization days of the patients and the endoscopy results, leucocyte and CRP values hasn't been determined.

Amaç: Gastrointestinal sistem kanamaları genellikle acil bir klinik tablodur. Gastrointestinal sistem kanamalarında mortalite % 5-12 arasındadır. Bu çalışmamızda GİS kanaması ile acil servisimize başvuran hastaların başvuru anındaki CRP, lökosit değerleri, endoskopi bulguları ve sosyodemografik özelliklerinin yatış süresine etkisi incelemeyi amaçladık. Gereç ve Yöntem: Eylül 2008-Aralık 2008 tarihleri arasında Selçuk Üniversitesi Meram Tıp Fakültesi Acil servisine başvuran ve üst gis kanamalı hastalar çalışmaya alındı. Hastalar; yaş, cinsiyet, yatış süresi, başvuru anındaki CRP, lökosit değerleri ile endoskopi bulguları yönünden değerlendirildi. Bulgular: Toplam 30 hasta çalışmaya alındı. Alt gastrointestinal sistem ve özafagus varis kanamaları olan hastalar çalışma dışı tutuldu. Gastrointestinal kanama ile başvuran hastaların %33'ü kadın, %67'si erkekti. Hastaların ortalama lökosit değerleri 11,06±4,06 k/uL ve ortalama CRP değerleri 35,77±26,56 mg/L idi. Bu hastaların hastanede ortalama yatış süreleri 6,40±6,17 gün olarak tespit edildi. En sık görünen endoskopik bulgular %70.0 evre 3, %3.3 evre 2b, %6.7 evre 2a, %13.3 evre1b ve %6.7 oranında evre 1a olarak tespit edildi. Sonuç: Çalışmamızda hastaların hastane yatış süresi ile endoskopi sonuçları, lökosit ve CRP değerleri arasında anlamlı bir ilişki bulunmamıştır.
Acil Servise Gastrointestinal Kanama İle Başvuran Hastalarda Hastane Yatış Süresini Etkileyen Faktörler